2003
DOI: 10.1093/cercor/13.8.837
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Contingency and Animacy from Simple Animations in the Human Brain

Abstract: Contingencies between objects and people can be mechanical or intentional-social in nature. In this fMRI study we used simplified stimuli to investigate brain regions involved in the detection of mechanical and intentional contingencies. Using a factorial design we manipulated the 'animacy' and 'contingency' of stimulus movement, and the subject's attention to the contingencies. The detection of mechanical contingency between shapes whose movement was inanimate engaged the middle temporal gyrus and right intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
132
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(149 citation statements)
references
References 33 publications
13
132
0
4
Order By: Relevance
“…In animacy research, a few studies have made use of displays from a side view (Csibra, Gergely, Bíró, Koós, & Brockbank, 1999;Gergely, Nádasdy, Csibra, & Bíró, 1995;Kuhlmeier, Wynn, & Bloom, 2003); however, the majority of studies have incorporated animacy displays viewed from overhead (Bassili, 1976;Blakemore et al, 2003;Bloom & Veres, 1999;Blythe et al, 1999;Castelli, Frith, Happé, & Frith, 2002;Gelman, Durgin, & Kaufman, 1995;Heider & Simmel, 1944;Tremoulet & Feldman, 2000), with other studies leaving the viewpoint ambiguous (Szego & Rutherford, 2007). It would appear that no previous research has made a direct comparison of ability to judge and perceive intentions across these two viewpoints.…”
Section: Methodsmentioning
confidence: 99%
“…In animacy research, a few studies have made use of displays from a side view (Csibra, Gergely, Bíró, Koós, & Brockbank, 1999;Gergely, Nádasdy, Csibra, & Bíró, 1995;Kuhlmeier, Wynn, & Bloom, 2003); however, the majority of studies have incorporated animacy displays viewed from overhead (Bassili, 1976;Blakemore et al, 2003;Bloom & Veres, 1999;Blythe et al, 1999;Castelli, Frith, Happé, & Frith, 2002;Gelman, Durgin, & Kaufman, 1995;Heider & Simmel, 1944;Tremoulet & Feldman, 2000), with other studies leaving the viewpoint ambiguous (Szego & Rutherford, 2007). It would appear that no previous research has made a direct comparison of ability to judge and perceive intentions across these two viewpoints.…”
Section: Methodsmentioning
confidence: 99%
“…The first reported that DNA methylation at the OXTR was predictive of an individual's neural response to biological motion (Jack et al, 2012). Specifically, higher levels of OXTR methylation were associated with significantly higher activation of temporal parietal junction and dorsal anterior cingulate cortex -regions previously reported to support social perceptual functions (Blakemore et al, 2003;Dichter et al, 2009). Puglia et al (2015) reported that high levels of OXTR methylation were associated with increased neural activity in limbic and face processing regions when viewing angry and fearful faces.…”
Section: Oxytocin Enhances the Salience Of Socially Relevant Sensory mentioning
confidence: 99%
“…Corroborating this supposition, the TPJ and STS, temporal poles and MPFC have all been implicated in mentalising processes in numerous studies, using a variety of methods and tasks (Gallagher & Frith 2003). Blakemore et al (2003) performed an infl uential fMRI study that employed simple shape animations to parse perceptions of animacy and contingency, as well as examine the effect of drawing attention to the contingency relations (via an explicit probe). Different parts of the brain were associated with viewing animate compared to contingent stimuli, and when both qualities were present activation was observed in superior parietal areas.…”
Section: Neuroimaging and The Intentional Stancementioning
confidence: 99%